Fatwa-fatwa M. Quraish Shihab dalam Bidang Hukum Islam - Mursalim, Mursalim; Madani, Abu Bakar (FENOMENA, 2013)
This study wanted to see about legal thought of Shihab in one of his book that discuss the issues of Islamic law , "M. Quraish Shihab Answering 1001 Islamic Problem You Should Knowâ. This study focuses on what methods he used in the legal ways of fatwa istimbath.Â  Shihab -as familiar as the figure in his thinking commentators- not just dwell on the tafsir world, but also in the legal world (Syarâi). It can be seen in a variety of legal ideas outlined in his book with many problems, ranging from worship to the social problems of society. In this study, the authors found that Shihab in the views of law as outlined in the book can enlighten the Islamic society to face the various problems faced which are explicitly described by the Quran and the Hadis.